Unidirectional guided-wave-driven metasurfaces for arbitrary wavefront control - Li, S.; K. L. Tsakmakidis; T. Jiang; Q. Shen; Zhang, H.; J. Yan; Sun, S.; Shen, L. (Nature Communications, 2024)
Metasurfaces are capable of fully reshaping the wavefronts of incident beams in desiredmanners.However,therequirementforexternallightexcitationand the resonant nature of their meta-atoms, make challenging their on-chip integration. Here, we introduce the conceptanddesignofafreshclassof metasurfaces, driven by unidirectional guided waves, capable of arbitrary wavefront control based on the uniquedispersion properties of unidirectional guided waves rather than resonant meta-atoms. Upon experimentally demonstrating the feasibility of our designs in the microwave regime, we numerically validate the introduced principle through the design of several microwave meta-devices using metal-air-gyromagnetic unidirectional surface magneto-plasmons, agilely converting unidirectional guided modes into the wavefrontsof3DBesselbeams,focusedwaves,andcontrollablevortexbeams. We, further, numerically demonstrate sub-diffraction focusing, which is beyond the capability of conventional metasurfaces. Our unfamiliar yet prac tical designs may enable full, broadband manipulation of electromagnetic waves on deep subwavelength scales.